2022
DOI: 10.3390/ph15101251
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Investigation of New N-Modified Spinorphin Analogs

Abstract: The emergence of diverse peptide derivatives has been due to constant efforts to find a specific peptide with pronounced biological activity for effective application as a therapeutic. Spinorphin-peptide products have been reported to possess various applications and properties. In the present study, spinorphin peptides with a rhodamine residue and a modification in the amino acid backbone were synthesized by a solid-phase method using Fmoc chemistry. The results obtained from the spectral and electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Along with determining the acid–base constants, calculating the partition coefficient (logP) is an essential parameter for explaining the in vivo functions of the biologically active molecules. [ 6 ] The “shake‐flask method” of analyte was placed in two immiscible phases: n ‐octanol and phosphate buffer solution with pH 7.4 and subsequent chromatographic (HPLC) detection using a calibration method of standard additives to determine the coefficients of the analytical function was used to assess logP of the studied compounds. The parameters for recording the analytical signals are described in Section 4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Along with determining the acid–base constants, calculating the partition coefficient (logP) is an essential parameter for explaining the in vivo functions of the biologically active molecules. [ 6 ] The “shake‐flask method” of analyte was placed in two immiscible phases: n ‐octanol and phosphate buffer solution with pH 7.4 and subsequent chromatographic (HPLC) detection using a calibration method of standard additives to determine the coefficients of the analytical function was used to assess logP of the studied compounds. The parameters for recording the analytical signals are described in Section 4.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that valorphine compounds have analgesic action by inhibiting pain receptors. [ 6 ] Furthermore, valorphine molecules have been displayed in mice to attenuate convulsive processes. [ 6 ] The possibility of the molecule passing through cell membranes or other subcellular structures is the basis for all the listed biological activities of the compounds, for which the structure and some physicochemical characteristics such as redox behavior, solubility, pH behavior, and AOA are important.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations